Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 1110332202 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "Year is greater than or equal to 1970", { "or" : [ "TaxonKey is Plantae", "TaxonKey is Animalia" ] } ] } The dataset includes 1110332202 records from 14610 constituent datasets: 12 records from Lepidoptera specimen database of Japan. 308173 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 2075 records from Leicestershire and Rutland Reptile Records to 2011. 45117 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 67 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 97 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 380261 records from Western Australian Museum provider for OZCAM. 3965 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 3 records from Parasitoides de Cochinilla. 81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 423 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2250548 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 2 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 2 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 16 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 5 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 33 records from Waldstück am Schullandheim Bad Bederkesa. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1459 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 1 records from Données naturalistes d'Olivier DELZONS. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1929 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 36 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 3 records from Society Islands beach bum black flies (Diptera: Simuliidae). 174 records from BIRDRACE Bon(n)apartemöwen. 9 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 1 records from Nannofossil abundance of Hole 75-532. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium. 2717 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 1545 records from NatureMap Calcrete Survey. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 28 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 515 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 71306 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 8930 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 10 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 6745 records from Hormigas del Museo de Entomología de la Universidad del Valle. 11 records from Reptiles Specimens of Akita Prefectural Museum. 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 97 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 167 records from UWIZM Snakes. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 78 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 86 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 17013 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 371 records from Heinersdorfer Sumpfwiese. 74481 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 269124 records from ARABEL - Arachnologia Belgica. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 15738 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 33126 records from Wolli Creek Preservation Society Bird Survey. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 470 records from MLZ Bird Collection (Arctos). 59 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 11 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 22 records from Microzooplankton abundance and biomass at station TT043_27-1. 166 records from Wiese am Waldrand (Gurtweil). 11 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 6 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 147049 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 6571 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 176 records from Renaturierung Werse (Innenbereich Beckum). 29 records from UWYMV Herpetology Collection (Arctos). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 10557 records from FUEL - Herbário da Universidade Estadual de Londrina. 90 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 10145 records from Midden-Limburg Fish Ponds Survey. 11209 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 11 records from Halocosa gen. n., a new genus of Lycosidae (Araneae) from the Palaearctic, with a redescription of H. cereipes (L. Koch, 1878). 12 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 4 records from marine sediment metagenome Raw sequence reads. 2 records from Herbarium Senckenbergianum (FR) - Fungi. 1985 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 20191 records from Seabirds in Norway - Estimated population sizes. 13 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 1177 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 3975 records from Leicestershire and Rutland Aculeate Records. 1 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 427 records from South Lanarkshire peatland records 2013. 8 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 10110 records from Suivi Temporel des Libellules (STELI). 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 1624 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 7950 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 67669 records from Données de l'Observatoire de la Faune de Bourgogne. 47 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 85 records from Neogene palynomorpha from site 93-603, part 2. 24387 records from Données de Luc BARBARO. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 116 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 239 records from Phenological Center - Birds (Murmansk). 95 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 5 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 1 records from Microbial diversity studies of Arabian Sea sediment. 50 records from Mokihinui and Karamaea small tributaries and seeps. 191 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 4142 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 231 records from Echinoderms from the Seaflower Biosphere Reserve. 829 records from If_Ecologie_Conseil_2017_12_18. 114 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 264 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 1 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 95252 records from Allan Herbarium (CHR). 38804 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1418 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 3839 records from Royal British Columbia Museum Entomology Collection. 1 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 420 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 280 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 21 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 29 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8409 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 6 records from NZCS Invertebrates New Collection After 1987. 2981 records from Colección Entomológica CDMB. 1151 records from Uncultured eukaryotes Targeted Locus (Loci). 253 records from Données naturalistes d'Olivier LAURENT. 22728 records from Restauración y conservación de Isla Guadalupe. 13612 records from Lepidoptera (Specimens NRM). 4192 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 219 records from Colección nacional de palmas de Colombia - JBQ. 993 records from ROC RSPB Farmland Species Survey Dataset. 98 records from Warnowtal (Rostock). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 205 records from Wild boar sightings held by Andy Riches. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 182049 records from Florida Keys Reef Visual Census 1999. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 3484 records from Marie-Victorin Herbarium (MT) - Bryophytes. 94 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 315 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 11227 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 205252 records from National Benthic Inventory. 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 195 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 16 records from Phenological Center - Fishes (Murmansk). 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 111 records from BIRDRACE Die Wendehälse. 21156 records from Tachinid Recording Scheme - GB and Ireland records. 27 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 21 records from Riedkanal Bötzingen. 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 26 records from Nannofossil abundance of Hole 60-458. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 3421 records from MEXU/Leguminosae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 158 records from Waldstück Bremerhagen LK Bio Kl. 12. 28 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 1013439 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 12 records from eDNA_Subseafloor. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 6 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 12 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 4 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 1960 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 663 records from A Catalogue and Historical Study of the Odonata of Ecuador. 347 records from Bannwald Burghauser Forst. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 37059 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 20382 records from SEWBReC Bees, Wasps and Ants (South East Wales). 2 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 8 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 4 records from Loricifera - SMF. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 17882 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 22 records from Benthic foraminifera and algae abundance of Hole 81-552A. 479001 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 9785 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 515 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1373 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 23 records from Morphologische Daten von Natrix. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 11364 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 825 records from UWIZM Molluscs. 26 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 3978 records from MCP-Aves - Coleção de Aves. 22 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 12 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 107 records from orthopteracollections-nhmj-ioj. 640 records from Bird specimens of Saitama Museum of Natural History. 308 records from CNAC/Coleccion Nacional de Acaros. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 7 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 104 records from Nannofossil abundance of Hole 37-334. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 59 records from Schulgelände SGD/Viersen. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 6103 records from Colecção Entomológica IIA. 56 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1291 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 16612 records from MZFC/Coleccion de Aves. 1 records from Nannofossil abundance of Hole 84-570. 53 records from Leopard and Weddell seal program 1999/2002. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 4294 records from Données naturalistes de Ségolène FAUSTEN. 54 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 2 records from Natural History Museum Maastricht (NL) - Herbarium. 52 records from DMNS Egg Collection (Arctos). 5634 records from MZL Invertebrate Collections. 4 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 54 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 11369 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 13329 records from Collection of Coleoptera. 73 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 717 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 1 records from Karpfenteich, Klasse 6d. 12 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 3 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 3547 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 35 records from A practical introduction to microbial molecular ecology through the use of iChips. 286 records from An updated checklist of aquatic plants of Myanmar and Thailand. 1702 records from BioGIS - Bryophytes - HUJ collections. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 543913 records from Queensland Museum provider for OZCAM. 37214 records from Herbarium Universitatis Daugavpiliensis. 1 records from 16S rRNA amplicon from marine Bacteria Raw sequence reads. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 38 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 20814 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 3125 records from Plecoptera. 16 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 1 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 701 records from Données naturalistes d'Arnaud LE NEVÉ. 23660 records from Swan Coastal Plain Survey. 1 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 1950 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 149 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 26159 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 14 records from NZCS Brownsberg Nature Park Monitoring. 1 records from Analyses of the recent components of sediment core PS1219-1. 717 records from Redland City Council Citizen Science Portal. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 4 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 215 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 339 records from HBRG Invasive Non-native Plants Dataset. 61572 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 165 records from Steinbruch Mainz-Weisenau, 3. Jahr. 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 15 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 951 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 43 records from Neogene palynomorpha from site 81-552. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 851 records from Pollen profile V and Ausfluss at Krumbach, Germany. 389 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 120 records from BIRDRACE The early birds. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 73702 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 1268 records from RECORD Orthoptera Data. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 66 records from Wildlife Sightings in the City of Logan. 7416 records from Birds Specimens. 26277 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 56 records from Schulgelände Kranich-Gymnasium (Salzgitter). 10 records from Oberservation of birds at station PS14/143 along 49° West. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 6979 records from Upper Silesian Museum, Bird Observations. 86 records from Fliegenhaupt Marksuhl. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 11144 records from DMNS Mammal Collection (Arctos). 1602 records from Données naturalistes de Quentin ROME. 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 116 records from SEWBReC Springtails and allies (South East Wales). 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 78 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 262 records from IBF Monitoring of Fungi. 84310 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 119 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 13377 records from National Museum of Natural Science. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 27 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 130 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 22052 records from CNIN/Abejas de México/Apoidea. 111 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 4156 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 27 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 1262 records from Flora útil del Municipio de la Huerta, Jalisco. 1302 records from Insectes Hyménoptères Scollidés de France. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 10 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 880 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1168 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4303 records from Weddell Sea macrozoobenthos EASIZ I. 681 records from IOW Natural History & Archaeological Society Marine Records. 272 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 1 records from Nannofossil abundance of Hole 10-93. 2189 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 12 records from Art´n Vielfalt im Kinderwald. 135 records from Waldi-Weiher. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 250791 records from Phase 2 Lowland Grassland Survey of Wales. 381 records from Invasive Non-Native Species, Outer Hebrides. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 470 records from Gewann Krampf (Heilbronn). 194 records from Naturalis Biodiversity Center (NL) - Crustacea. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 17 records from Benthic macrofauna abundance of sediment core 13201-002. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 111 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 607 records from Inventory of Bassila forest (North-Benin). 26 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 30 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 3 records from The larva of Lestes alfonsoi Gonzalez & Novelo (Zygoptera: Lestidae). 1078 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1282925 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 411861 records from DATAVES. 2 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 3792 records from Heliconiine Butterfly Collection Records from University of Cambridge. 27 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 464 records from The Broward College Insect Collection. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 14 records from Berea College, Ralph L. Thompson Herbarium. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 1 records from Distribution of nanoplankton at trap WR2. 79 records from Birdrace-Bielefinken-Bielefeld. 13624 records from Ecosphère_2017_12_18. 107 records from Müritz-Nationalpark. 125 records from Range table from ostracoda in ODP Hole 143-866B. 4021 records from Fish specimens of Toyama Science Museum. 14 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 11 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 5145 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 265 records from Wald am Schloss Wittgenstein Bad Laasphe. 503 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 70103 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 64352 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 223 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 790 records from Isle of Wight non-native invasive species. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 3 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 580 records from Floristic records in the Moscow and Novgorod regions. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 816 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 99 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 711 records from Données naturalistes de François BRETON. 814 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 9 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 58 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 58 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 46 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 7 records from Die Bachspezies 2008/2009. 1536 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 61 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 352 records from hauterivian_echinoids_of_the_paris_basin. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 99 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 12 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 1166 records from TransForest - vegetation, lichen and fungi data 2016. 10524 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 30 records from UWIZM Anoles. 3 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 126 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 33 records from Biodiversity of springs and rock seepages 2003. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 25816 records from Biowide Species data. 430 records from Pollen analysis of sediment profile TR0 from Truennensee. 1194 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 2375 records from Macrobenthos Chukchi Sea, 1986. 10 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 203 records from Condamine Alliance. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 521 records from Schanzenanlage Bergham. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 14 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 10 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 1145 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 21 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 43 records from Faunal assemblage of sediment core TR149-31. 14 records from Microbial community in marine sediments. 152 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03. 18 records from Naturtag. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 2 records from Herbier Louis-Marie (QFA) - Collection de lichens. 22 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 1 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 165061 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 6 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 3 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 8332 records from Scotland Otter Survey Database. 17 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 4617 records from Données de type contact de Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 204796 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 908 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 1284 records from Données naturalistes de Thomas LORICH. 5772 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 4 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 6 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 55 records from Galls on Beech Trees in Hainich, 2008. 2039 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 26039 records from CAS Entomology (ENT). 1787 records from Naturalis Biodiversity Center (NL) - Pisces. 216367 records from Carnet B Lorraine. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 30 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 3 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 308761 records from Seasearch Marine Surveys in England. 53 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 122 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 61 records from Nannofossil abundance of Hole 10-94. 118 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 298 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 7 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 847 records from Collection Trichoptera - SMF. 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 33 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 144 records from Range table from nannofossils in ODP Hole 164-994C. 128 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 2 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 1 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 96 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 8 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 2759 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 12846 records from MCP - Coleção de Abelhas. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 26 records from Erhard Sopp. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Charinus rocamadre (Amblypygi, Charinidae): description of the female, ultrastructure of the male and female gonopods, and mitochondrial DNA sequences. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 45 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 99 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 4 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 61 records from Shrews of Poland. 180 records from Données naturalistes de Pascal Dupont. 5925 records from K-State Museum of Entomological and Prairie Arthropod Research. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 40 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 147 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 181089 records from Marine benthic dataset (version 1) commissioned by UKOOA. 77 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 973 records from Freshwater Fishes of Bulgaria. 5353 records from European Moth Nights. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 1186 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 8425 records from NBMB Herps. 874 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 172 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 434 records from Aves de Caño Cristales, La Macarena, Meta. 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 290 records from Umgebung der Gesamtschule Hamburg-Winterhude. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 1005 records from BUND - Dassower See (Lübeck/Dassow). 6 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 12 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 346 records from Birds and plant species near Petushki town (Vladimir region). 759 records from Revues diverses et littérature grise.. 2 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 53786 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 526 records from Expedición Providencia I - INVEMAR. 10 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 39 records from Lindesnes. 6042 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 23589 records from University of Michigan Museum of Zoology, Division of Birds. 512 records from UWYMV Bird Collection (Arctos). 1570838 records from Hatikka Observation Database. 16 records from Foraminifera abundance of Hole 61-462. 568 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 109821 records from inatura - Erlebnis Naturschau Dornbirn. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 11 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 1 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 25 records from Collection Graptolithina fossil SMF. 787 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 9 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 7 records from Sea water microorganisms Raw sequence reads. 398 records from Specimen Database of Colorado Vascular Plants. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 22 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 2 records from Global Ocean Sampling Expedition. 90 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 69 records from BIRDRACE Pfeifenten. 50 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 39 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 2265 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 239 records from Knechtweide (Kohlfurth). 14 records from Collections ichtyologiques et herpétologiques (BOUM). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 85 records from MCP-Mamiferos - Coleção de Mamíferos. 20 records from Foraminifera abundance of Hole 64-481. 12 records from Nannofossil abundance of Hole 29-281. 24 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 79508 records from Butterflies of Ireland. 17 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 562 records from Rare plants database extract from Scottish Natural Heritage. 73 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 819 records from Coléoptères Silphidés du département du Loiret. 1116 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 68290 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 24230 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 46 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 4 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 476 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 43 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 70 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 16 records from Hazel Dormouse in Ireland. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 67789 records from CAS Invertebrate Zoology (IZ). 17 records from water Raw sequence reads. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 27 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 6 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 39308 records from Insects, Outer Hebrides. 714 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 99 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 46 records from An der Ohm, (Wettsaasen). 172 records from Community structure of Archaea in the western North Pacific and the Arctic Ocean. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 111 records from Сypripedium guttatum Sw. in the Komi republic. 7439 records from BioGIS - Vascular plants - Israeli Gene Bank. 10 records from Nannofossil abundance of Hole 73-521A. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 9990 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 11 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 7346 records from NSW South Coast & ACT plants. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 16 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 4 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 16739 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 505 records from National Frog Survey of Ireland 2010/2011. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 568 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 3628 records from Colección Ornitológica de la Universidad del Valle. 305 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 2525 records from Marine Turtles. 574 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 155 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 499 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 14 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 13 records from Nannofossil abundance of Hole 67-499B. 19 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 41676 records from Tagged Seal Location Data from SOGLOBEC. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 3409 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 2588 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 3 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 881 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 170 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 1709 records from The Gibson spider collection. 34 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 101 records from Naturgrundstück (Eutin). 3 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 7 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 193 records from Truppenübungsplatz Panzerkaserne Böblingen. 135 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 1 records from The Calliphoridae (Diptera) of Armenia. 651 records from Réseaux écologiques/Trame verte et bleue. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 1129915 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 10 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 5 records from The endemic Southern African genus Epirinus Dejean, 1833 (Coleoptera: Scarabaeidae: Scarabaeinae) revisited: five new species and two new synonyms. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 49 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 62 records from Zoo Frankfurt. 2333 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 163 records from Canada_BasinMegabenthos2002. 4 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 682 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 3 records from Fungal Records Database of Britain and Ireland. 1081 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 1 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 7 records from Nannofossil abundance of Hole 30-285A. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 15 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 152 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 49786 records from La familia Asteraceae en México. Fase VI. 10 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 20779 records from WTSWW Data: All Taxa (West Wales). 172 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 412246 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 63 records from Marine gastropod distribution from patagonian shallow waters. 190 records from "Ahrschleife bei Altenahr". 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 3 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 210379 records from South Australian Museum Australia provider for OZCAM. 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 3 records from A new species of forest-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from the Indawgyi Wildlife Sanctuary, Kachin State, Myanmar. 510 records from Inventaires des cygnes du département de l'Eure. 23 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 9921 records from CSIRO, fish surveys by the Soela, 1980s. 27 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 60 records from Artenvielfalt in der Kinderakademie im RFZ. 4 records from A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan. 4 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 22 records from Microfossil abundance of Hole 16-158. 1616 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 25 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 53062 records from British Antarctic Survey Argos satellite tracking data. 77 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 10298 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1100 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 14 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 600 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 16 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 6901 records from University Of Pretoria: Lacewing Database Project (1911-2015). 48 records from Freiheitsring (Frechen). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 2 records from Nannofossil abundance of Hole 66-490. 2783 records from USAC Mammals Collection. 1 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 6992 records from Stone-curlew Annual Surveys. 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 121 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 3108 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 97 records from Avifauna asociada a las fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 1186 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 1 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 192 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 9319 records from Données naturalistes de Franck NOEL. 80 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 35 records from Nannofossil abundance of Hole 82-558A. 1470 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 7 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 342 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 3320 records from BioGIS - Mammals - SPNI. 610 records from Carnarvon Basin wetland survey. 19 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 1617 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 90194 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 2 records from A revision of the Costa Rican species of Stenoeurilla Brailovsky & Barrera (Hemiptera: Heteroptera: Coreidae: Stenoscelideini), with the description of two new species, new distributional records, synonymical note, and key to the known species. 909975 records from SEWBReC Birds (South East Wales). 265 records from Luderbusch. 43299 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 807 records from Área Galeras - Monitoreo de Aves, 2016. 1643 records from Collections data on ecology of bottom animal of the Southern ocean. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 117 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 14 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 3214 records from Collection Echinodermata SMF. 112150 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5017 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 232 records from Malawi-Cicindelidae-Biodiversity-Data. 2353 records from Fish Collection of Yokosuka City Museum. 3 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 11 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 18074 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 4 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 31 records from Living Cirripedia. 9 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2017 records from Helmintos parásitos de peces del sureste de México. 61 records from Naturpark Kottenforst-Ville 15.6.09. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 1302 records from Amundsen Gulf Overwintering Eukaryote Community. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 78 records from Roter Berg Werdau (Leubnitz). 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 3755 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 10 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 169 records from FFH-Gebiet Klosterwasser/Burkau. 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 15929 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 353 records from Données naturalistes de Hubert GUIMIER. 1717 records from Collection rousset -1947-2013. 1860 records from Données naturalistes de Hervé BOUYON. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 386 records from Thistle Heads and Ermerged Insects. 57 records from CSIRO Yellow Box Fragmentation Project. 78 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 19568 records from Entomology Collection at the Natural History Museum of Utah. 2196 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 78752 records from ALCB - Herbário Alexandre Leal Costa. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 114 records from BIRDRACE LiLaLau. 3693 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 4 records from Comparative morphology and taxonomy of the tiger moth genus Epanycles Butler (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina), with notes on related genera. 57998 records from Fish specimens of Kagoshima University Museum. 39345 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 119 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 2458 records from UTEP Invertebrates (Arctos). 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 59 records from Schulteich Freie Waldorfschule Darmstadt. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 22 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 1 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 1032 records from Étude entomologique des forêts publiques de Martinique, pour l'ONF. 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 1648 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 100 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1194891 records from First Bird Atlas. 20232 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15156 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 1095 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 204 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 8705 records from University of Ghana - Ghana Herbarium. 4170 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 1 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 359 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 31 records from Lepidurus arcticus survey Northeast Greenland 2013. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2807 records from Natura 2000 Vallée de la Seille. 7439 records from Inventario de Hymenóptera; parasítica en México. 153 records from VSN-Wiese. 32 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 20 records from 3Soil16S. 910 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 4793 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 705 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 181977 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 9 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 76 records from BIRDRACE Nachtigallen. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 1 records from Dinoflagellate abundance of Hole 28-274. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 5 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 76 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 16 records from Marine planktonic ciliates: SSU rDNA. 336 records from Lucanidae. 1 records from R. L. McGregor Herbarium Lichen Collection. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 26267 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 68 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 5570 records from UAM Fish Collection (Arctos). 219 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 8808 records from Survey of bumblebees in central Alberta - 2018. 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 70 records from Isotope tracer experiment: meiofauna counts. 19 records from Données naturalistes de LE GLOANEC Vincent. 21888 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 6279 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 282 records from Deponie Klausdorf. 47 records from Schulgelände (Wetter). 7 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 3093 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 1 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 14199 records from Enquête Lucane. 860 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 873 records from Erlengraben/Lipp-Tal (Östringen). 16 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1263 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 1684 records from Herbier National de Guinée (HNG). 7 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 391 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1484 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipaility – Norway; 1996 – 2017 based on systematic catches with ordinary mouse traps in traplines. 7356 records from EDIT - ATBI in Gemer area (Slovakia). 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 43 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 1 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 21754 records from Global compendium of Aedes albopictus occurrence. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 451 records from BioGIS - Reptiles - HUJ collections. 82 records from Teich Berlin Wuhlheide. 54 records from Nannofossil abundance of Hole 27-259. 1 records from Analyses of the recent components of sediment core PS1222-1. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 149 records from AKG-Gelände (Bensheim). 3 records from E1 Targeted Locus (Loci). 645237 records from Flora Atlas N.T.. 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5007 records from Fishes in the Argentine Sea from 1967 to the present time. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4864 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 243 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 226 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 3 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 182 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 19598 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 529 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 342 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 993 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 10 records from Ostracoda abundance of Hole 32-306. 3 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 210 records from Lebensraum Gesamtschule (Langerwehe). 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 569 records from Pollen analysis of sediment core GeoB6518-1. 3 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 80 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 47903 records from Arizona State University Hasbrouck Insect Collection. 128 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 1105 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 2536 records from Invasive Alien Species Occurrence in Ghana. 63364 records from CCAMLR historic KRILL. 243 records from Quarrendorfer Landschaftsschutzgebiet. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 162 records from Registros de quirópteros de tres localidades del caribe colombiano. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3576 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 240 records from Chironomid remains in the sediment sequence of Site PG1212. 1033 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 3379 records from Lista florística de la Costa Grande del estado de Guerrero. 16 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 42 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 71 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 304 records from Equatorial Pacific Ocean Targeted loci environmental. 87535 records from MDFRC macroinvertebrate survey. 234 records from Données naturalistes de Pauline BALDUCCI. 62 records from Amtsrain Apolda-Zottelstedt. 25 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 40135 records from DIBA-Parc del Montnegre i el Corredor. 4761 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 1 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 5 records from Planktic foraminifera abundance of Hole 40-362A. 56 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 1610 records from JRS Wetands data Rwanda, 2019. 18 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 35 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 21194 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 7 records from Grundwasserlebensraum im Englischen Garten (München). 1152 records from Inventario de macroalgas de Isla Guadalupe, México. 209 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 6 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 14971 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 82 records from Meniscus Midges (Dixidae) of Ireland. 63078 records from Norwegian Lepidoptera working group. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 23 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 6172 records from NE Scotland fish records 1800-2010. 224 records from Natura 2000 PnrL. 10798 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 116 records from Zambian Bat Collections Worldwide. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 30913 records from Vascular plants of south-central China. 143 records from BIRDRACE Punkbirder Helgoland. 6 records from Sächsische Schweiz (Pfaffenstein). 11955 records from Données ONEMA BDMAP 2014. 565 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 554 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 27 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 1594 records from MEXU/Flora de Oaxaca. 12 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 5768 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 11 records from marine sediment metagenome Raw sequence reads. 660 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 20 records from Heavy minerals of sediment core PL94-64. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 132045 records from Amphibiens et Reptiles de France (Enquête 2). 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 7178 records from Ravensthorpe Range survey data. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 5 records from Schulinnenhöfe (Gelsenkirchen). 160 records from Wirbach-Taubental (Bad Blankenburg). 1450 records from Données naturalistes d'Alain BERLY. 24294 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 2 records from Nanoplankton abundance at station GeoB2012-5. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 1698 records from Red-throated diver national surveys in Scotland - raw data. 89 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 834 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 10698 records from Yoann_BLANCHON_2017_12_18. 14792 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 530727 records from Données de la flore d’Alsace (SBA). 3 records from MSB Mammal Observations (Arctos). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4968 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 237 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 61519 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Données naturalistes de Sophie COHEN. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 3864 records from Wikiplantbase #Sicilia. 33 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 25 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 1 records from Nannofossil abundance of Hole 25-249. 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 9 records from Fatkullina imitata n. sp., second species of a unique cheilostome bryozoan genus with reversed-polarity zooidal budding, and new family Fatkullinidae. 994 records from CNIN/Tipos Coleoptera. 4 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 246 records from BARTH-Environnement_2017_12_18. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 278 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 6 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 12 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 25 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 44 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 4737 records from SANBI: DNA Banking(1987-2011). 21 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 65 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 20325 records from The national database for marine data (MADS). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 198 records from Naturalis Biodiversity Center (NL) - Mammalia. 16 records from Bacterial Diversity in the East China Sea. 2 records from Nannofossil abundance of Hole 9-82. 16 records from Microzooplankton abundance and biomass at station TT043_11-1. 8 records from Foraminifera abundance of Hole 57-440A. 40 records from Nannofossil abundance of Hole 74-525A. 2658 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 4 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 101 records from BIRDRACE Enger am Spektiv. 337 records from Ghent university - Zoology Museum - Nematod Collection. 12 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 18 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 6016 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 7 records from Stadtrandlandschaft Apolda-Nord. 23 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 63 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 4513 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 322193 records from Florida Keys Reef Visual Census 2010. 5608 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 337 records from Pollen data of trap CB4. 1481 records from Leicestershire and Rutland Mature trees Inventory 2011. 10 records from Valentin Moser Bats. 153 records from annex1. 5 records from Dinoflagellate abundance of Hole 28-270. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 126 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 62 records from Rare vascular plant species in North-West of Kostroma region, Russia. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 130 records from Draubiotop Lavamünd. 21180 records from Extracellular DNA marine sediment Targeted Locus (Loci). 4 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 25 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 549 records from Netzfluegler_Raw1. 314 records from "Schwarzwassertal" bei Pobershau. 5 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 1 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 25545 records from Plan de vertebrados de la Patagonia. 2 records from A revision of the genus Petta Malmgren, 1866 (Annelida: Pectinariidae), with two new species from deep waters of southeastern Australia, and comments on phylogeny of the family. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 92 records from Birdrace_TerraCamper-Münster. 557 records from Corn bunting breeding distribution in Scotland. 14 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 616 records from Whale catches in the Southern Ocean. 357 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 817 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 30431 records from River Biologists' Database (EPA). 49805 records from CABI Africa Invasive and Alien Species data. 7469 records from Eurobodalla Regional Botanic Gardens. 152 records from Selztal bei Friesenheim. 40012 records from Banded Iron Formation and Greenstone survey data. 41 records from Great Eastern Ranges - Slopes to Summit. 18 records from Microzooplankton abundance and biomass at station TT045_19-3. 1384 records from UCM Mammal Collection (Arctos). 53 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 97788 records from Tiroler Landesmuseum Ferdinandeum. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 490 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 121 records from BIRDRACE Immerwiederhopf. 3 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 11 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6445 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 37 records from Caracterización de Reptiles de las lagunas del municipio del Medio Baudó. 5 records from Collection Malakologie - SMNG. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 47 records from Données d'observation de phanérogames marines en Martinique. 75 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 354 records from Antarctic and Subantarctic Asteroid zoogeography. 24 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 315 records from Coastal and Marine Species Database. 28 records from Nannofossil abundance of Hole 67-499. 59 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 128156 records from Tasmanian Museum and Art Gallery provider for OZCAM. 403 records from TTRS Mammals. 54 records from Weidegebiete in der Selzrenaturierung. 744 records from Ostracoda in sediment core PS51/159-10. 7 records from Bacterial community dynamics during polysaccharide degradation at contrasting sites in the Southern and Atlantic Oceans. 5 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 834295 records from Liste des espèces de la faune sauvage (Amphibiens, Mammifères hors Chiroptères, Oiseaux, Orthoptères, Reptiles & Rhopalocères) observées selon le maillage communal français de la base de données naturalistes Faune-France .. 22 records from Avifauna de los bosques húmedos y remanentes de Tierralta - Córdoba, 2011. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 233 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 1811 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 3 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 355 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 1192 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 190 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 2441 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 9 records from UTEP Fish (Arctos). 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 40 records from The caddisfly genus Protoptila in Costa Rica (Trichoptera: Glossosomatidae). 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 92804 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 12916 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from University of Sindh Jamshoro Herbarium. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 49 records from Faunal assemblage of sediment core TR149-32. 35 records from Nannofossil abundance of Hole 15-149. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 1868 records from Registros Primates Neotropicales Convocatoria APC. 8 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Anammox bacteria in sediment cores of Daya Bay, China. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 12 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 15691 records from Mollusques dulcicoles de France - Jacques MOUTHON. 708 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 610 records from BID-Malawi-Geometridae-Biodiversity-Data. 13 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 49 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 123 records from Collection Aves (bird skins) SMF. 1 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 46 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 5791 records from La familia Asclepiadaceae en México. 4054 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 6 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 9 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 26 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 370 records from Otter survey of Ireland 2004 & 2005. 2443 records from JOI - Herbário Joinvillea. 2 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 1052 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 12 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 84 records from BIRDRACE Vogelscheuchen. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 81 records from Birdrace-Die_Ornithomaten-Herford. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 909 records from Área Galeras - Monitoreo de Aves abril-octubre, 2018. 160 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 78045 records from NINA Vanndata fisk. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 47 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 5 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 817 records from AlgaTerra. 1314 records from Records from the South Australian Seed Conservation Centre. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 304531 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 1 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 923 records from Danielsberg (Mölltal, Kärnten). 73 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 1 records from Nannofossil abundance of Hole 39-353A. 16988 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 191 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 34 records from Borkhart. 154 records from HSU Vertebrate Museum Mammals Collection. 153 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 3459 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 3 records from Nannofossil abundance of Hole 9-80. 35 records from ADDOMEx. 1 records from New Prionospio and Laubieriellus (Annelida: Spionidae) species from Southeastern Brazil. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1945 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 17 records from Foraminifera abundance of Hole 57-440B. 1703 records from 成龍溼地魚類生態紀錄. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6570 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 235 records from Rutilans. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 6191 records from UTEP Insects (Arctos). 3278 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 624 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 13357 records from Leicestershire Bryophyte Data. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 5 records from Données naturalistes de DURON Cyril. 41096 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 5678 records from Collection Pisces SMF. 1 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 239 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 18224 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 1245 records from Gemeinde Sursee. 15 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 33 records from Nannofossil abundance of Hole 67-496. 1223 records from Insect specimens of Omogo Mountain Museum. 852 records from OMMAG_Suivi_Dauphins_Les_Saintes. 508 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 166 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 4512 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 794 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 837 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 1 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 2 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 352 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 69 records from Inventario de Mamíferos Mámbita. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 11592 records from Canadian Museum of Nature Mammal Collection. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 235 records from Pollen and spore abundance of Hole 42-381. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 207977 records from Estonian Nature Observations Database. 189 records from Naturpark Sternberger Seenland. 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 162239 records from Biodiversitätsdatenbank des Landes Salzburg. 27 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 7850 records from NCSM Mammals Collection. 3 records from Nannofossil abundance of Hole 52-418. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 73 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 4312 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 897 records from DMNS Parasite Collection (Arctos). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 1 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 19 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 3161 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 13 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 74 records from Nannofossil abundance of Hole 64-476. 1335 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 7231 records from Colección general del plantas vasculares del Herbario JBB. 2188 records from Données naturalistes de Matthias COLIN. 20 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 89798 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 5 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 151158 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 186 records from Cowan Tetrapod Collection - Herpetology. 200173 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 12448 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 6 records from Phytoplankton abundance at station CD46_0705C#4. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 4168 records from CASES2003_2004. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 29 records from Hemmerder Schelk (Unna). 38429 records from Fife Nature Records Centre combined dataset. 1 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 52 records from CHAS Botany Collection (Arctos). 1 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 15 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) — three possibly threatened Brazilian species. 43 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 78437 records from Natural History Museum, Vienna - Herbarium W. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8847 records from Odonata records from RSPB Reserves 1970-2009. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 1038 records from Données supplémentaires Atlas des Mammifères marins. 2695 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 9870 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 10370 records from Protist Diversity in the East China Sea. 18 records from Anfibios presentes en el Cerro Jánano. 22 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1599417 records from NBIS Records to December 2016. 3 records from Abundance of radiolaria at station UT99-23-2. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 52 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 1748 records from Floral visits on plants, InsectScale 2008. 2347 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 270 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 162261 records from Arizona State University Vascular Plant Herbarium. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 1165 records from Stoneworts in Wales. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Fungi Collection. 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 22 records from Ostracoda abundance of Hole 24-238. 21 records from Thirteen new records of ferns from Brazil. 4 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 388 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 3561 records from Biogeography of near-shore reef fishes in northern New Zealand. 2619 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 191 records from Steinbruch Mainz-Weisenau, 2. Jahr. 24 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 8803 records from NE Scotland other invertebrate records 1800-2010. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 2174 records from ConDidact Citizen Science Surveys - Snails 2006. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 28 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 97 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 52 records from Brock University Herbarium (BU). 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 30257 records from SIO Benthic Invertebrate Collection. 7115 records from Whicher Scarp Flora Survey. 405736 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 8648 records from DASSH Data Archive Centre volunteer survey data. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 69 records from Unter hellen Zinnen und finsteren Grotten. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 11 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 212 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 572 records from Phenological Center - Birds (Laplandskiy). 29 records from Abundance of benthos infauna at station POS128/2_284. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 528 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 15 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 1924 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 97031 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 693344 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 54 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27988 records from Bird records for Argyll for the years 2002 and 2003. 4227 records from Données naturalistes de Loïc SALAUN. 1137 records from SWECO. 18 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 27 records from Ibaraki Nature Museum, Fish collection. 25 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 15790 records from EAC - Herbário Prisco Bezerra. 2206 records from East Ayrshire Species Database. 28485 records from Marine Biological Sample Database, JAMSTEC. 450 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 301 records from Otter (Lutra lutra), Outer Hebrides. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 956 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 3 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 1567 records from Collection Crustacea - ZMB. 66 records from Range table from ostracoda in ODP Hole 151-910D. 874 records from The Living Murray Fish data. 612 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 500 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 1850 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 13 records from jamaica_invasive_alien_species. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 1 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 14 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 35 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 270 records from BIRDRACE Niederlausitz-Team. 4803 records from Odonata de Veracruz. 1 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 4 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 5 records from Planktic foraminifera abundance of Hole 18-173. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 332 records from Poissons et Crustacés d'eau douce de la Martinique. 6217 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 327 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 157 records from Loup 2009 présence régulière communale (réseau Loup-Lynx ONCFS). 383 records from LACM Invertebrate Paleontology. 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 5 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 3724 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 635 records from CG04_2017_12_18. 734 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 213 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 22 records from Microzooplankton abundance and biomass at station TT045_15-2. 10204 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 1016 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 5 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 300 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 94807 records from Denver Museum of Nature & Science - Entomology. 13 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 2084 records from Occurrence data of tree species for crystalline Mountain Forest of Tanzania.. 19 records from Nannofossil abundance of Hole 47-398. 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 840 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 420 records from Relative abundance of ostracods in sediment core St09. 6 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 21 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 24 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 36 records from BIOMEO_2017_12_18. 1 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 41 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 152 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 1 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 224 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 2394 records from All herbarium specimens of grasses held at TAN herbarium. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 495 records from Pollen counts of sediment core GeoB9503-5. 4 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 876 records from Bosque Mesófilo de Montaña de México. 233 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 329 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 53 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 4054 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 97 records from Landschaftspark St.Leonhard-Deisendorf. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 2269 records from Vermont Buprestidae Survey. 522188 records from Parc_National_de_Port_Cros_2017_12_18. 15236 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 2000 records from Diversidad y distribución de los copépodos (Cyclopoida) de las zonas áridas del Centro-Norte de México. 11 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 1643 records from MPM Milwaukee Public Museum Herbarium. 3 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 13 records from Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific. 1 records from Collection ornithologique A. Maës. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1117 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 32 records from Mammal specimens of Komatsu City Museum. 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 10 records from Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 270 records from ACT and Southern Tablelands Weed Spotter. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 12546 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 41 records from Örtzemündung (Stedden). 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 51 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 30233 records from National Stag Beetle Surveys (Great Stag Hunts). 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 2860063 records from Eremaea. 86524 records from Marine Offshore Seabed Survey data held by JNCC. 3566 records from FrogWatch SA. 35816 records from KUBI Ornithology Collection. 86 records from Données naturalistes de Françoise SERRE-COLLET. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 708 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1121 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 899 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 4 records from Pelagic Gulf of Mexico Targeted loci environmental. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 926 records from MEXU/Tipos de plantas vasculares. 29 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 23 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 2 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 345 records from Packer Collection /Madagascar. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 2223 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 2484 records from NIWA Invertebrate Type Collection. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 11 records from ALP-PAGES_2017_12_18. 35 records from Species of Gnathophausiidae (Crustacea, Lophogastrida) collected off the west coast of Baja California, Mexico, during the TALUD cruises. 23 records from Ackerrain Plönhagen. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 5748 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 4258 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 220 records from Malawi-Histeridae-Biodiversity-Data. 1992 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 149 records from Schiller Gymnasium Hof 10b. 488 records from Biologische Station im Kreis Wesel. 728 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 1718 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 1390 records from The Apterygota collection (EA) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 22 records from Bachabschnitt der Nette (Osnabrück). 16 records from Microzooplankton abundance and biomass at station TT043_4-1. 4 records from Benthic foraminifera and algae abundance of Hole 35-325. 91600 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 36 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 8 records from Revision of the Eurybrachidae XIV. The Australian genera Olonia Stål, 1862 and Stalobrachys gen. nov. (Hemiptera: Fulgoromorpha). 46 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 61 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 2805 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 216 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 3567 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 750 records from Carabidae of the European North-East of Russia. 103 records from BIRDRACE federleser. 5016 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 4 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 25 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 504 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 6 records from Abundance of benthos infauna at station GIK23065-1. 17562 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 2697069 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 8 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 952 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 227 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 1 records from Range table from planktonic foraminifers in ODP Hole 175-1084A. 24 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 6724 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 148 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 388871 records from BioFokus. 15261 records from Anymals+plants - Citizen Science Data. 203 records from Chronicle of Nature - Phenology of Insects of FSBI Zeya State Nature Reserve. 1288 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 9179 records from Tartu University, palaeontology collections. 1 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 3387 records from Données avifaune de Guadeloupe. 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 23 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 309 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 3500 records from UMNH Reptiles and Amphibians Collection (Arctos). 1577 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 662 records from CNAN/Scorpiones. 2 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 487 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 38446 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 825 records from DBG Tissue and DNA Bank. 114 records from BIRDRACE Di-Bi-Di-Birder. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 1 records from A new species of Orthosiphon (Lamiaceae) from Angola. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 1 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 3 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 7 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 86 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 3 records from Nannofossil abundance of Hole 20-200. 46 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 243 records from Thistles species and abundance. 1 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 31916 records from Mollusca of Costa Rica (INBio). 2 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 2084 records from Flora vascular acuática de la cuenca del Río Tamesí. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 10 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 814 records from flower availability 2008 Hainich. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 14 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 777 records from Données naturalistes de Stéphane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 8393 records from Andes to Amazon Biodiversity Program. 1 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 237 records from WildesMoor bei Schwabstedt. 336 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 7 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 625 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 7 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 14511 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16380 records from Database for alien invasive plants occurrences in Germany. 18 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 41 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 603 records from Capture of Primary Biodiversity Data for West African Plants. 44 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1 records from Revision of the amphiamerican genus Mysidium Dana, 1852 (Crustacea: Mysida: Mysidae), with descriptions of two new species and the establishment of two new subgenera. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1372 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 14 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 8311 records from 成龍溼地鳥類生態紀錄. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 190 records from Herpetofauna laguna El Tinije. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14691 records from Ontario Breeding Bird Atlas 1981-1985. 123 records from Birdrace-Professorenteam-Münster. 6903 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 2840 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 3 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 5 records from A new genus with three new species of free-living marine nematodes of the subfamily Desmodorinae (Nematoda: Desmodoridae), from the continental shelf off northeastern Brazil. 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 235302 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 516 records from Données naturalistes de Laurent KREMMER. 4 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 447 records from Biological Collection, National Institute of Oceanography, Goa, India. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 134 records from Pollen profile II/B at Krumbach, Germany. 244 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 720 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 150 records from Steinbruch Mainz-Weisenau. 1203 records from Palynological analysis of sediment core GeoB3910-2. 21157 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 3321 records from Fauna y flora del municipio de Lipa, Arauca. 72 records from Macroalgas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 1 records from Japanese Pseudosmittia Edwards (Diptera: Chironomidae). 92 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 4 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 23 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 9 records from Distribution of meiobenthos in sediment core M19_202-2 of the northeastern Atlantic (Table 1). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 12844 records from Israeli Butterfly Monitoring Scheme (BMS-IL). 27 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 137 records from Inventaire de la faune aviaire et de l'Ichtyofaune de la mare de l'Abarkaizé et des Oiseaux de Dan Saga. 523 records from Anfibios de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 1 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 3639 records from Fish: Records for Kent.. 4 records from Nannofossil abundance of Hole 39-353. 16 records from Description of Paracymbiomma gen. nov., a new genus of prodidomid spiders from the Neotropical region (Araneae: Prodidomidae) including a new troglobite species. 38 records from Was lebt in der Brutzwiese?. 28 records from Biodiversity Surveys, South-east Arnhem Land. 282 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 3 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 36 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 14 records from Benthic macrofauna abundance of sediment core 13200-045. 6 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 2217 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 37 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 3 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 86 records from Données naturalistes de Pierre-Alexis RAULT. 60 records from Wichita State University Collection. 32175 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 7 records from New and interesting species of sacculonotic Haplozetidae (Acari, Oribatida, Haplozetidae) from Indonesia. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 25 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 222046 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 28 records from Halophila stipulacea in the Caribbean Sea. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 91 records from Données naturalistes de Bastien TRAN. 1 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 74 records from pbzt_insect_biodiversity. 8 records from Insect specimens of Himeji City Science Museum. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 57 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 2 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 217 records from NZCS Upper Tapanahony Expedition 1991. 26 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 203 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 3 records from Revision of Camarota Meigen (Diptera: Chloropidae), with a new species from Uganda. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 1 records from Two new species of Amphiglena (Sabellidae, Annelida), with an assessment of hidden diversity in the Mediterranean. 142 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 9 records from New species of the genus Gnathochorisis Förster (Hymenoptera: Ichneumonidae: Orthocentrinae) from the Neotropical Region. 75 records from Abundance of algae in the Aral Sea. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 27734 records from Lizard Island Research Station. 29 records from Naturerfahrung. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 24 records from Hidden diversity of giant scydmaenines: five new species and new records of Clidicus in the Philippines (Coleoptera, Staphylinidae, Scydmaeninae). 53 records from Coleção de Nematoda do Museu Nacional - UFRJ. 29161 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 92 records from Range table from benthic foraminifers in ODP Hole 159-962D. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 6644 records from Inventory of plant species through Benin (West Africa). 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 896 records from Data on agroforestry plant species of Benin. 1266 records from Insectes Hyménoptères Formicidés de Corse. 15 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 3459 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 16 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5588 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 3 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 970 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 3 records from A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae). 17 records from Benthic macrofauna abundance of sediment core 13078-013. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 2550 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 8055 records from ZooplanktonBeaufortSeaNOGAP2. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 150 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 2205 records from Jardín Botánico Atlántico, Gijón: JBAG. 16 records from Microzooplankton abundance and biomass at station TT045_26-3. 849 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 34 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 105 records from Fish Fauna of Berlin. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 104 records from Phytoplankton abundance in surface water during cruise CD61. 1995 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 6581 records from Nijmegen Natural History Museum (NL) - Herbarium. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 2445048 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 445 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 1170 records from Département_du_Var_2017_12_18. 127 records from Wildlife Observations Bardon Hill 31.5.09. 70 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 42457 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 56 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 2 records from CTD water column metabarcoding. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 27 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 42 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 68 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 1948 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 4 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 173135 records from Finnish Floristic Database (Literature Sources). 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 130 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 58028 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 10714581 records from iNaturalist Research-grade Observations. 27 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 170496
Keywords: GBIF; biodiversity; species occurrences